JIWA KEWIRAUSAHAAN DAN INOVASI PRODUK PADA IKM KERUPUK RAMBAK DI BANGSAL MOJOKERTO - Wahyuningsih, Roy (STKIP Persada Khatulistiwa Sintang, 2023)
Maintaining an enterprise's success requires increasing the entrepreneur's spirit. The enhanced entrepreneurial spirit, combined with improved product innovation, will benefit IKM's operations in the Mojokerto district's Bangsal Village. The purpose of this study is to determine the impact of the entrepreneurial spirit and product innovation on the success of the Rambak Crackers IKM Business in Bangsal Village, Mojokerto Regency. This study takes a quantitative method. A saturated sample of 73 owners Rambak Crackers IKM Business in Bangsal Village was used for sampling. Methods of data collection include observations, interviews, questions, and documentation.Double regression analysis was employed in this study, which included descriptive statistical analysis, validity tests, reliability tests, classical assumption tests, double linear regression analyses, hypothesis tests, and determination coefficients. The results of the study show that there is an influence of an entrepreneurial spirit on the success of the rambak crackers IKM business; there is an influence of product innovation on the success of the rambak crackers IKM business; and there is the influence of the entrepreneurial spirit and product innovation on the success of the rambak cracker IKM business in the village of Bangsal, Mojokerto Regency